Pengaruh Kualitas Pelayanan terhadap Kepuasan Pasien pada Puskesmas Pakan Kamis Tilatang Kamang Kabupaten Agam - Siska, Adilla Juita (Jurusan PIPS FKIP UMMY Solok, 2018)
This study aims to determine the magnitude of Service Quality Impact on Patient Satisfaction of Pakan Kamis Public Health Center District Tilatang Kamang Agam.. The population in this study were patients using BPJS card whose Health Facility in Level I was registered at Pakan Kamis Public Health Center. In connection with the purpose of the above research, we hypothesized that